필수지방산 결핍이 유도된 기니피그에서 보라지유와 홍화유 섭취의 표피 과증식 억제 및 세라마이드 대사에 미치는 효과 비교 - 이세령(Lee, Se Ryung); 조윤희(Cho, Yunhi) (Journal of nutrition and health, 2015)
Purpose: Borage oil (BO) and safflower oil (SO) are efficacious in reversing epidermal hyperproliferation, which is caused by the disruption of epidermal barrier. In this study, we compared the antiproliferative effect of dietary BO and SO. Altered metabolism of ceramide (Cer), the major lipid of epidermal barrier, was further determined by measurement of epidermal levels of individual Cer, glucosylceramide (GlcCer), and sphingomyelin (SM) species, and protein expression of Cer metabolizing enzymes. Methods: Epidermal hyperproliferation was induced in guinea pigs by a hydrogenated coconut diet (HCO) for 8 weeks. Subsequently, animals were fed diets of either BO (group HCO + BO) or SO (group HCO + SO) for 2 weeks. As controls, animals were fed BO (group BO) or HCO (group HCO) diets for 10 weeks. Results: Epidermal hyperproliferation was reversed in groups HCO + BO (67.6% of group HCO) and HCO + SO (84.5% of group HCO). Epidermal levels of Cer1/2, GlcCer-A/B, and ${β}$-glucocerebrosidase (GCase), an enzyme of GlcCer hydrolysis for Cer generation, were higher in group HCO + BO than in group HCO, and increased to levels similar to those of group BO. In addition, epidermal levels of SM1, serine palmitoyltransferase (SPT), and acidic sphingomyelinase (aSMase), enzymes of de novo Cer synthesis and SM hydrolysis for Cer generation, but not of Cer3-7, were higher in group HCO + BO than in group HCO. Despite an increase of SPT and aSMase in group HCO + SO to levels higher than in group HCO, epidermal levels of Cer1-7, GlcCer-A/B, and GCase were similar in these two groups. Notably, acidic ceramidase, an enzyme of Cer degradation, was highly expressed in group HCO + SO. Epidermal levels of GlcCer-C/D and SM-2/3 did not differ among groups. Conclusion: Dietary BO was more prominent for reversing epidermal hyperproliferation by enhancing Cer metabolism with increased levels of Cer1/2, GlcCer-A/B, and SM1 species, and of GCase proteins. 본 연구에서는 기니피그에 8주간 필수지방산 결핍 식이 공급에 의해 표피 과증식을 유도한 후 계속된 2주간의 보라지유 또는 홍화유 식이 공급에 의한 과증식 억제 및 Cer, GlcCer, SM의 표피 함량 및 세라마이드 대사 관련 효소들의 단백질 발현 변화를 정상대조군인 BO군 및 필수지방산 결핍 군인 HCO군과 비교하였으며 그 결과는 다음과 같다. 1. 8주간의 필수지방산 결핍 식이 공급 후 계속된 2주간의 보라지유 식이 공급 (HCO + BO군)은 2주간의 홍화유 식이 공급에 (HCO + SO군) 비해 더욱 현저히 표피 과증식을 억제하였다. 2. 10주간 필수지방산 결핍식이를 공급한 HCO군은 정상대조군인 BO군에 비해 Cer의 총 함량 및 Cer1/2/5/6/7, GlcCer-A/B의 함량이 유의적으로 감소되었다. HCO + BO군의 Cer과 GlcCer의 총 함량 및 Cer1/2, GlcCer-A/B, SM1의 함량은 HCO군에 비해 유의적으로 증가한 반면 HCO + SO군의 이들 함량은 HCO군과 유사하였다. GlcCer-C/D, SM의 총 함량 및 SM 2/3의 함량은 군간 변화가 없었다. 3. HCO군에서는 GCase 발현이 감소한 반면 HCO + BO군에서는 현저히 증가하였다. HCO + SO군의 aSMase의 단백질 발현이 HCO군에 비해 유의적으로 증가하였으나 aCDase의 발현 또한 다른 군에 비해 현저히 증가하였다. HCO + BO군과 HCO + SO군 모두 SPT의 단백질 발현이 HCO군에 비해 유의적으로 증가하였다. 결론적으로 표피 과증식이 유도된 기니피그에 보라지유 식이 공급은 GlcCer-A/B을 포함하는 GlcCer 총 함량, SM1 및 GCase의 발현 증가와 더불어 Cer1/2를 포함하는 Cer 총 함량을 증가시켜 궁극적으로 표피 과증식을 현저히 억제하였다.